Desaın Character Concept Dengan Menggunakan Bıtmap Graphıc: Case Study Mobıle Legends Bang-Bang - Tony Wibowo; Darwin Darwin (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Character art is now commonly found in social media and in our lives. In general, character art is found in entertainment media in the form of video games, and there is also in movies, comics, k-pop fans, and many more. Most character art is created using bitmap graphics using the Adobe Photoshop application. This study uses a qualitative method, by observing the use of bitmap graphics in the character art of a video game with the aim of studying the making of the character art. It can be concluded from this research that the use of bitmap graphics in making character art and other art concepts is still very much needed to produce good art.